THE DIGITAL KAZAKHSTAN. THE DEVELOPMEMT OF HUMAN RESOURSES IN EDUCATION - Kushzhanov, N. V.; Balginova, K. M.; Maydangalieva, Z. A.; Satygalieva, G. B.; Mahammadli, Dashqin (Scientific Journal of Pedagogy and Economics, 2018)
The digitalization is strategic priorities of development in all around a world. According to the leading world experts, by 2020 a quarter of the world economy will be digital, and implementation of the digital technologies in economy allowing the state, business, and society to interact effectively. Development of the human resources will create a new generation of patriots with excellent ICT skills. This program is one of the strategic directions of Digital Kazakhstan economy development. Governments can play an essential role in enhancing digital literacy through the country's primary education system. Digital literacy skills lead to stronger creativity, selfexpression and improved interpersonal relations, and provide a foundation for the responsible use of technologies. Some of the main barriers to broadband ICT development are the high prices of the Internet, the lack of an enabling policy environment, high costs of infrastructure, low revenue potential and low digital literacy rates. Today a considerable number of people uses the Internet, origin and promoting of social networks generally erased age and frontiers of the virtual communication of people. Social communities are one of the most exciting services existing on a network today. One of the successfully implementable tasks of social networks is the combining of users on shared interests. Another task is filling with a network various information. For teachers, the social networks are the set of opportunities – discussion of current problems of education, for example, implementation of new State standard teaching programs, representation in networks of own methodical development, creative pupils works and also the experience exchange. There is a massive number of different judgments whether it is worth "retracting" generally once again children in the virtual communication. The modern IT technologies provide the whole list of tools for communications of teachers with pupils not only in school hours but also behind walls of schools. Abroad mobile means of communications with a class through the program on the smartphone or a pad – pretty favorite thing. The Black Board and Canvas services, known in the USA, integrate schools and campuses. The closest to them in essence and to contents – the School student mobile application which serves as a site for combining of schoolmates together with their class teacher. Education of children of a primary school age develops on an electronic network model more and more active today. Implementation in introductory classes of the computer, mobile devices, and software applications transfers ordinary handling real objects to the virtual graphics space, and internal communication – in remote interaction through services and resources of communication of the Internet, including in social networks. Conclusions had addressed access to information and communications technologies for different groups of children, the importance of digital literacy, online safety concerns and other issues.